"UV-curing of novel tri-functional melamine-phosphate oligomer: An effect of coating with polyurethane acrylate toward mechanical, thermal, and flame retardant properties". (16th February 2022) - Mali, Pundalik; Sonawane, Narendra; Nilesh Pawar,; Patil, Vikas
A novel melamine-phosphate tri-functional acrylate (MPTO) was successfully synthesized via cyclization reaction of hexamethylolmelamine (HMM) with phosphorous oxychloride (POCl3 ) followed by addition reaction of hydroxyethylmethacrylate (HEMA). The molecular structure of MPTO was identified by FTIR and 1H-NMR, 13C-NMR, and GC-MS spectra. The synthesized MPTO oligomer was impregnated with polyurethane acrylate to make various formulations and UV cured on wood and galvanized steel panels. The results of UV cured films from differential scanning calorimeter (DSC) and thermo-gravimetric analysis (TGA) exhibited increase in thermal stability and highest char yield of 18.4% at 800°C. The diffused diffraction peak appearing around 2ϴ = 16–22° corresponds to an amorphous structure which leads to irregular arrangement with formation of strong cross-linking polymer network. Furthermore, all coating films show prominent flame retardancy with UL-94 V-0 rating and maximum limiting index (LOI) values of 34.8%. The polyurethane acrylate (PU) coatings cured with MPTO that exhibited excellent mechanical properties were estimated using various tests such as adhesion, pencil hardness, solvent resistance, flexibility, and corrosion test. The coating performance revealed that MPTO can improve the mechanical, thermal, and flame retardant properties because of its unique structure identity of melamine-phosphate moiety and long aliphatic segment of an acrylate ester. Graphical Abstract